A critical review of the IMF's tools for crisis prevention - Roberto Marino; Ulrich Volz (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Against the backdrop of the International Monetary Fund's (IMF) increasing focus on crisis prevention measures and the G20's discussion of “global safety nets”, this paper analyses the IMF's tools for crisis prevention, with particular emphasis on the recently developed Flexible Credit Line (FCL) and Precautionary Credit Line (PCL). The paper reviews why it took the Fund so long to develop crisis prevention facilities that would find subscribers and scrutinises initial experiences with the FCL and PCL. Moreover, it discusses the systemic implications of and problems associated with such crisis prevention facilities and examines why only so few countries are using these facilities thus far. Based on this analysis, it offers policy recommendations for the development of the IMF's crisis prevention facilities.
Keywords: 330; Internationales Finanzsystem; Regionale + globale + transnationale Governance